Strategic Communication for Institutional Legitimacy, Governance Reform, and Stakeholder Trust in Higher Education Organizations - Flores, Junas Dungog; Fabrica, Reah G. (International Review of Management and Marketing, 2026)
Development communication plays an important role in shaping inclusive institutional cultures by facilitating dialogue, participatory engagement, and strategic organizational communication within higher education institutions. This study examined how development communication operates as a strategic mechanism for negotiating identity, strengthening institutional legitimacy, and enhancing stakeholder trust among transgender educators in higher education organizations in Metro Cebu. Using a qualitative interpretivist paradigm, the research employed a multiple-case study design involving 25 transgender educators across five universities representing public, private, and faith-oriented institutions. Data were collected through focus group discussions and in-depth interviews and analyzed using reflexive thematic analysis. The findings revealed five major themes: legitimacy construction, risk-managed identity strategies, cultural change through identity leadership, stakeholder perception alignment, and governance reform and institutionalization. Results indicate that transgender educators employ communicative practices such as dialogic engagement, pedagogical advocacy, and relational leadership to navigate institutional barriers and influence organizational communication processes that shape institutional culture and stakeholder perception. Despite structural constraints and policy inertia, development communication enables educators to transform marginalization into communicative agency that contributes to governance reform and inclusive institutional practices. The study demonstrates that inclusive communication practices extend beyond interpersonal interaction and play a strategic role in strengthening institutional legitimacy, stakeholder trust, and organizational sustainability. The findings provide managerial and institutional insights for higher education leaders on how strategic communication and inclusive governance practices can enhance institutional credibility and stakeholder engagement.